A global classroom? evaluating the effectiveness of global virtual collaboration as a teaching tool in management education - Taras, V.; Caprar, D. V.; Rottig, D.; Sarala, R. M.; Zakaria, Norhayati; Zhao, F.; Jimenez, A.; Wankel, C.; Lei, W. S.; Minor, M. S.; Bryla, P.; Ordenana, X.; et al. (Academy of Management, 2013)
We evaluate the effectiveness of global virtual student collaboration projects in international management education.Over 6,000 students from nearly 80 universities in 43 countries worked in global virtual teams for 2 months as part of their international management courses.Multisource longitudinal data were collected, including student and instructor feedback, course evaluations, assessment of changes in knowledge, attitudes, and behaviors following the experiential project, and various indicators of individual and team performance.Drawing on experiential learning, social learning, and intergroup contact theories, the effectiveness of the experiential global virtual teambased approach in international management education was evaluated at the levels of reactions, learning, attitudes, behaviors, and performance.The findings show positive outcomes at each level, but also reveal challenges and limitations of using global virtual team projects for learning and education. Implications for international management education and suggestions for future research are discussed.